Neighborhood Racial Characteristics, Credit History, and Bankcard Credit in Indian Country - Valentina Dimitrova-Grajzl; Peter Grajzl; A. Joseph Guse; Richard M. Todd; Michael Williams (Center for Economic Studies and ifo Institute (CESifo), 2015)
We examine whether concerns about lenders' discrimination based on community racial characteristics can be empirically substantiated in the context of neighborhoods on and near American Indian reservations. Drawing on a large-scale dataset consisting of individual-level credit bureau records, we find that residing in a predominantly American Indian neighborhood is ceteris paribus associated with worse bankcard credit outcomes than residing in a neighborhood where the share of American Indian residents is low. While these results are consistent with the possibility of lenders' discrimination based on community racial characteristics, we explain why our findings should not be readily interpreted as conclusive evidence thereof. We further find that consumer's credit history is a robust and quantitatively more important predictor of bankcard credit outcomes than racial composition of the consumer's neighborhood, and that the consumer's location vis-à-vis a reservation exhibits no effect on bankcard credit outcomes.
Keywords: G21; J15; P43; R11; 330; bankcard credit; American Indian reservations; discrimination; neighborhood racial characteristics; credit history